Clinical, Laboratory and Radiographic Features Associated With Prolonged Hospitalization in Children With Complicated Appendicitis - Bhattacharya, Jyotsna; Silver, Ellen J.; Blumfield, Einat; Jan, Dominique M.; Herold, Betsy C.; Goldman, David L. (Frontiers in Pediatrics, 2022)
Objective: In children with appendicitis, rupture of the appendix is associated with a significant increase in morbidity. We sought to characterize the spectrum of illness in children with complicated appendicitis and to define those factors associated with a longer hospital stay. Study Design: We conducted a retrospective review of 132 children, 18 years of age or younger at a large urban teaching hospital in the Bronx, NY between October 2015 and April 2018 with an intraoperative diagnosis of perforated appendix. Clinical, laboratory and radiologic findings were reviewed, and the primary study outcome was length of stay (LOS) dichotomized at the median, which was 7 days. Statistical analyses were done to characterize morbidity and define variables predictive of longer stay. Results: Children with LOS > 7 days experienced significantly more morbidity compared to those with shorter LOS, including the need for ICU transfer. A longer duration of symptoms prior to presentation was associated with a longer stay. Multivariable logistic regression analysis indicated that the presence of abscess and presence of free fluid in the right upper quadrant (RUQ FF) on initial imaging and C-reactive protein (CRP) level >12 at admission, were independently associated with a longer stay. Conclusion: There is considerable variation in the morbidity of complicated appendicitis. The association between longer stay and initial imaging findings along with an elevated CRP may provide a useful tool in identifying those children at risk for worse outcomes.